Effect of Herding Behaviour on Stock Price Movements at Nairobi Securities Exchange - Ngumi, Patrick; Kazungu, Khatibu; Mutasa, Felician (International Journal of Economics, 2022)
Purpose: Empirical evidence shows that herding pattern is experienced at NSE which is linked to particular periods. Methodology: We observe the kind of herding characterised by changes in the stock market parameters which includes number of deals, average price, total purchases among other market parameters are as a result of unique circumstances as opposed to the overall market. Findings: Further, results of both CSSD and CSAD indicated that herding has an effect on prices of shares and stocks. Idiosyncratic herding phenomenon detected can either be reduced or eliminated from portfolios through different diversifications strategies which are meant to reduce the levels of exposure to risk by merging various investment like bonds, real estates, stocks among others which are all not likely to be moving towards the same direction. Further, by encouraging diversification, also herding behaviour would be decreased by the simple fact that assets cannot move in the same direction at the same time and rate. Unique Contribution to Theory, Practice and Policy: It is also recommended that the government should try to privatize some of its enterprises to enhance public participation in an effort to stabilise stock prices. This should be accompanied by alliances with exchange securities. The policy makers need further to consider forecasting the financial instability and thus regulate herding patterns in advance.